How to define and meet blood pressure targets after traumatic brain injury: a narrative review - Kartal, Ahmet; Robba, Chiara; Helmy, Adel; Wolf, Stefan; Aries, Marcel J. H. (Neurocritical care, 2024)
Traumatic brain injury (TBI) poses a significant challenge to healthcare providers, necessitating meticulous management of hemodynamic parameters to optimize patient outcomes. This article delves into the critical task of defining and meeting continuous arterial blood pressure (ABP) and cerebral perfusion pressure (CPP) targets in the context of severe TBI in neurocritical care settings.